Biochemical derangement in twin pregnancy : complete hydatidiform mole and viable foetus - Munirah Md Mansor; Khalidah MB; Dian Nasriana Nasuruddin; Hanita O (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Case of co-existence of twin pregnancy of complete hydatidiform molar with viable intrauterine pregnancy is extremely rare with low incidence of 1 case for 20,000 – 100,000. It is associated with high risk of spontaneous abortion, preterm delivery, intrauterine death, bleeding, pre-eclampsia, and persistence trophoblastic disease (PTD). It may associate with biochemical derangement that may induce symptomatic manifestation to the mother. There are few cases reported in Asia population with significant clinical dilemma and management to the maternal and foetus. Here, we report a case of a young woman with previous bad obstetric history who presented with antepartum per-vaginal bleeding and was noted to have a twin pregnancy with complete hydatidiform molar and viable foetus. It was complicated with markedly elevated human chorionic gonadotropin (hCG) and hyperthyroidism. Postpartumly, her hCG level was persistently high and her condition progressed into gestational trophoblastic neoplasm.